Firearms Fetishism in Texas: Entanglements of Gun Imaginaries and Belief - Butters Albion M. (Brill, 2022)
This chapter examines firearms fetishism as a complex assemblage of gun imaginaries and belief. Understanding fetishism as tightly intertwined with religion and shifts in gun culture over the past half century, the discussion focuses on Texas and its predominant forms of Christianity, and demonstrates the connection between gun ownership and religiosity. Drawing on research materials and interviews with Texas residents at a pair of universities in Austin, the chapter also examines the significance of two shootings in churches in Texas before and after a recent law (Senate Bill 535) that allows concealed and open carry in public places of worship. In this way, the chapter analyzes the nature of the gun owner’s relationship with the object and what it symbolizes. As viewed through the lens of fetishism theory, this may involve an explicitly religious aspect, commodification, or even a sexualized interpretation. Invoking existing gendered ideals of the hero archetype, firearms fetishism is revealed to play a fundamental role in the construction and expression of moral and religious identity in Texas.
Up in Arms: Gun Imaginaries in Texas